Jordan and the Terrorist Threat of DAESH 2003-2017 - Khamees, Fawaz Bil’as; Rogers, Roy Anthony (Dirasat: Human and Social Sciences, 2025)
Objectives: This paper provides an in-depth analysis of the DAESH terrorist threat to Jordanian national security. In particular, it focuses on its transnational terrorist threat, ideology, and strategy towards the Jordanian society. It also addresses some Jordanian issues that may be relevant to Jordan's strong presence on the DAESH agenda, such as its geographical location and economic, social, and demographic factors, in an attempt to understand the evident targeting of Jordan from 2003-2017 in terms of recruiting Jordanian citizens as foreign fighters under its banner. Methods: This paper applies the descriptive analytical method and qualitative content analysis by systematically collecting data related to Daesh from a set of books, newspapers, speeches, interviews, and social media posts to investigate the group's motivations for targeting Jordan’s security and its citizens. Results: The study reveals that DAESH was well aware of the reality of Jordanian society and its challenges; as a result, it was able to infiltrate Jordan by intensifying the recruitment of Jordanians to carry out terrorist acts and engage in terrorist activities between 2003 and 2017. Conclusions: The group’s tenets are rooted in transnational strategies, recruitment, religious inspiration, fanaticism, effective media and propaganda, and indiscriminate targeting. The group's generic principles can be exploited to create a predictive framework to fortify the domestic front, including adopting a comprehensive national plan of action to address the terrorist threat and an effective reintegration plan for returnees, in order to deter, mitigate, or neutralize terrorist attacks.